Gastric adenocarcinoma predictive long intergenic noncoding RNA (GAPLINC) promotes oral cancer stemness by acting as a molecular sponge of miR331-3p - Kuang-Yuan Liang; Ni-Yu Su; Hsiu-Pin Yang; Pei-Ling Hsieh; Chih-Yuan Fang; Lo-Lin Tsai; Yi-Wen Liao; Chia-Ming Liu; Cheng-Chia Yu (Elsevier, 2024)
Background/purpose: Accumulating evidence has suggested that treatment failure of cancer therapy can be attributed to cancer stem cells (CSCs). Among numerous regulators of cancer stemness, non-coding RNAs (ncRNAs) have gained significant attention recently. In this study, we examined the role of gastric adenocarcinoma predictive long intergenic noncoding RNA (GAPLINC) in oral CSCs (OCSCs). Materials and methods: RNA Sequencing and quantitative real-time polymerase chain reaction (qRT-PCR) were used to determine the expression of GAPLINC. Flow cytometry and sphere-forming assay were exploited to isolate OCSCs. Measurement of aldehyde dehydrogenase 1 (ALDH1) activity, CD44 expressing cells, and various phenotypic assays, such as self-renewal, migration, invasion, and colony-forming abilities, were conducted in CSCs of two types of oral cancer cells (SAS and GNM) following the knockdown of GAPLINC. A luciferase reporter was also carried out to validate the direct interaction between GAPLINC and microRNA (miR)-331-3p. Results: Our results showed that GAPLINC was overexpressed in OCSCs from patient-derived and oral cancer cell lines. We demonstrated that silencing of GAPLINC in OCSCs downregulated various CSC hallmarks, such as ALDH1 activity, percentage of CD44-expressing cells, self-renewal capacity, and colony-forming ability. Moreover, our results revealed that the effect of GAPLINC on cancer stemness was mediated by direct repression of miR-331-3p. Conclusion: These data have potential clinical implications in that we unraveled the aberrant upregulation of GAPLINC and demonstrated that suppression of GAPLINC may reduce cancer stemness via sequestering miR-331-3p.